Makna Istilah Sebutan Untuk Tuhan “YHWH“ Sesembahan Umat Beriman di Kitab Perjanjian Lama - Andreas Danang Rusmiyanto (ICHTUS: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Abstract: The name of Allah is an issue that often intersects with dogma. In the religion understoodor known as YHWH, Addonay is translated as god. For that name is very sacred to all who are called.But God wanted his creation to know him so he introduced his name to his people in various ways,mentioning the essence of the name. The purpose of this scientific work is to describe one of thenames of God, especially the book of Exodus 6:2 and the use of the expression in several books of theOld Testament. The research methodology of this scientific article uses qualitative methods byanalyzing the meanings of terms and words. Given the majesty of Allah's name, any use of Allah'sname that insults Him and His attributes is an attack on Allah's name. The third commandment of theTen Commandments forbids taking God's name in vain as it shows a lack of respect for God Himself.According to God in His statement, anyone who abuses God's name is "guilty" (Exodus 20:7). In theOld Testament, God's name was dishonored when someone failed to fulfill a promise or oath made inHis name (Leviticus 19:12). A person who uses Allah's name to confirm his oath, but does not fulfillhis promise, is showing disrespect to Allah and is not afraid of His retribution. Basically the same asdenying the existence of God. The name of God represents His glory, His majesty and His divinity.We must honor and worship his name just as we honor and worship God himself. Otherwise, we willuse his name in vain.Keywords: God's Name, YHWH, Sacred, Old Testament, ten commandmentsAbstrak: Nama Allah menjadi isu yang sering bersinggungan dengan dogma. Di dalam Kekristenanyang dipahami atau dikenal sebagai YHWH, diterjemahkan Addonay seperti dewa. Untuk nama itusangat sakral bagi semua yang dipanggilnya. Tetapi Tuhan ingin ciptaannya mengenalnya sehinggadia memperkenalkan namanya kepada umatnya dengan berbagai cara, menyebutkan esensi darinama itu. Tujuan dari karya ilmiah ini adalah untuk mendeskripsikan salah satunya nama Tuhan,khususnya kitab Keluaran 6:2 dan penggunaan ekspresi dalam beberapa buku Perjanjian Lama.Metodologi penelitian artikel ilmiah ini menggunakan metode kualitatif dengan menganalisis maknaistilah dan kata. Mengingat keagungan nama Allah, setiap penggunaan nama Allah yang menghinaDia dan sifat-sifat-Nya adalah penyalahgunaan nama Allah. Perintah ketiga dari Sepuluh Hukummelarang penyebutan nama Tuhan dengan sembarangan karena menunjukkan kurangnya rasahormat kepada Tuhan itu sendiri. Menurut Tuhan dalam pernyataannya, siapapun yangmenyalahgunakan nama Tuhan adalah "bersalah" (Keluaran 20:7). Dalam Kitab Perjanjian Lama,nama Tuhan dicemarkan ketika seseorang gagal memenuhi janji atau sumpah yang dibuat atasnama-Nya (Imamat 19:12). Seseorang yang menggunakan nama Allah untuk menegaskansumpahnya, tetapi tidak memenuhi janjinya, menunjukkan sikap tidak hormat kepada Allah dantidak takut akan pembalasan-Nya. Pada dasarnya sama saja dengan mengingkari keberadaan Tuhan.Nama Tuhan mewakili kemuliaan-Nya, keagungan-Nya dan keilahian-Nya. Kita harus menghormatidan menyembah nama-Nya sama seperti kita menghormati dan menyembah Allah sendiri. Jika tidak,kita akan menggunakan namanya dengan sia-sia.Kata kunci: Nama Allah, YHWH, Sakral, Perjanjian Lama, sepuluh hukum